B is for bonnet [large type] - Gray, Shelley Shepard (Gray, Shelley Shepard. Amish ABCs, 2025)
"Raised by their divorced, lapsed-Amish father and English mother, siblings Jonny, Martin, Kelsey, and Beth can't wait to reinvent their lives. The four don't have much in common, but they long for the stable sense of family they felt when visiting their New Order grandparents, Josiah and Sylvia Schrock, in peaceful Holmes County, Ohio. And the Schrocks couldn't be more surprised when the grandkids want to try living with them -- and joining their faith . . . When Jonny hears startling news about his health, he knows it's past time to change his life. Quitting college, he unexpectedly finds the fulfilling job of his dreams. And he's instantly smitten with cafe owner Treva Kramer, whose baked goods are as warm and delicious as her lively personality. But no matter how hard Jonny tries, he can't seem to get past her secret sadness and distrust. Can he prove that his feelings for her are for real -- and forever -- in time? A bad breakup left Treva heartbroken -- and resolved to be independent without relying on anyone ever again. Exhausted from pouring everything she's got into her cafe, she's stunned by Jonny's easygoing ways -- and drawn to his optimistic nature. But when she thinks his real interest is in becoming Amish, she's even more determined to stay focused -- and keep her heart safe . . ."--